2019
DOI: 10.1002/wsbm.1476
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of genomic imprinting: Epigenetic control of mammary gland development and postnatal resource control

Abstract: Genomic imprinting is an epigenetically regulated process leading to gene expression according to its parental origin. Imprinting is essential for prenatal growth and development, regulating nutritional resources to offspring, and contributing to a favored theory about the evolution of imprinting being due to a conflict between maternal and paternal genomes for the control of prenatal resources—the so‐called kinship hypothesis. Genomic imprinting has been mainly studied during embryonic and placental developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 105 publications
1
9
0
Order By: Relevance
“…While Grb10 suppresses growth in offspring, it increases milk production in mother ( Cowley et al, 2014 ). Hanin and Ferguson-Smith (2020) support the idea suggested by Stringer et al (2014) according to which mammary gland represents the functional equivalent of the placenta in the postnatal stage of eutherian mammals, contributing then to the development and growth of offspring. Indeed, mammary gland, by providing milk to the newborn, contributes further to maternal effects on offspring phenotypes, in addition to those that occur during fetal life.…”
Section: Harnessing Livestock Resources For a Fuller Picture Of The I...supporting
confidence: 82%
See 1 more Smart Citation
“…While Grb10 suppresses growth in offspring, it increases milk production in mother ( Cowley et al, 2014 ). Hanin and Ferguson-Smith (2020) support the idea suggested by Stringer et al (2014) according to which mammary gland represents the functional equivalent of the placenta in the postnatal stage of eutherian mammals, contributing then to the development and growth of offspring. Indeed, mammary gland, by providing milk to the newborn, contributes further to maternal effects on offspring phenotypes, in addition to those that occur during fetal life.…”
Section: Harnessing Livestock Resources For a Fuller Picture Of The I...supporting
confidence: 82%
“…Milk provides the neonate with essential nutritional components and non-nutritional bio-active components, such as growth factors including IGF2 that has been shown to be an important biological regulator of milk production in dairy cattle ( Berkowicz et al, 2011 ). Many studies, mainly in mice, showed that the maternal-offspring interface through lactation is a critical period, suggesting that genetic variation and maternal diets may affect milk composition, leading to lasting effects with alteration of lifelong health ( Hanin and Ferguson-Smith, 2020 ; Rodríguez-González et al, 2020 ; Lean et al, 2022 ).…”
Section: Harnessing Livestock Resources For a Fuller Picture Of The I...mentioning
confidence: 99%
“…These include a better understanding of the early evolutionary history and diversification of GI. A closer look at GI in certain taxa and tissues through integrative omics approaches could for example help clarify the constraints applied to imprinted clusters, the mechanisms that enabled the acquisition of DMRs and the role of transposable elements in the evolution of mammalian development ( Bogutz et al, 2019 ; Hanin and Ferguson-Smith, 2020 ; Hanna and Kelsey, 2021 ; Senft and Macfarlan, 2021 ). Comprehensive genome scans for imprinted genes in species with little or no previous evidence for GI bring important information, since it promotes the understanding of both GI evolution and related phenomena such as methylation reprogramming and allele-specific expression, which regulate key biological processes in vertebrates ( Frésard et al, 2014 ; Zhuo et al, 2017 ; Skvortsova et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those pups become obese and grow faster than control pups, due to upregulated milk protein synthesis in mice that lack the imprinting regulation. Finally, Hanin hypothesised, that the mammary gland, the source of postnatal nutrition, is similar to the placenta, the prenatal nutrition source, where both have a high rate of parentally imprinted genes [ 20 ].…”
Section: Meeting Reportmentioning
confidence: 99%